2012
DOI: 10.1371/journal.pone.0049643
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Extrahepatic Biliary Atresia in an Open-Access Medical System

Abstract: IntroductionBiliary atresia (BA) is the most common cause of cholestatic jaundice in infancy. Early diagnosis and surgical management, ideally before 60 days of age, result in improved outcomes. We aimed to determine the age at diagnosis of BA in the Military Health System (MHS) and to compare the age at diagnosis by access to care models. We hypothesized that children with BA receiving primary care in military facilities have an earlier age at diagnosis due to decreased economic and access barriers.MethodsDat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…A study in Seattle Washington reported a median age of referral for biliary atresia to be 61 days with a mean of 51 days which was rather late attributed to delays in investigating neonatal jaundice and acholic stools and this declines the success of portoenterostomy 8,9 . This sharply contrasts the situation in the industrial world where the median age at diagnosis is 40 days and median age at Kasai operation is between 54 and 69 days of age 10 .…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…A study in Seattle Washington reported a median age of referral for biliary atresia to be 61 days with a mean of 51 days which was rather late attributed to delays in investigating neonatal jaundice and acholic stools and this declines the success of portoenterostomy 8,9 . This sharply contrasts the situation in the industrial world where the median age at diagnosis is 40 days and median age at Kasai operation is between 54 and 69 days of age 10 .…”
Section: Discussioncontrasting
confidence: 60%
“…21/46 (45%) presented with one of the following complications at admission; failure to thrive, sepsis, ascites, liver cirrhosis, and portal hypertension. This reflects complete lack of screening strategy for biliary atresia as reported in some come countries by using colored (chromatic) cards with a stool color scale distributed to parents 6,7,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, preterms with multifactorial cholestasis may have grey stools, and biopsy results with bile duct proliferation may also resemble BA (21,22). Despite the foregoing, prematurity itself seems not to affect the timing of BA detection (23), but merely delays the timing of the KPE (4). Our results emphasize that one of the main challenges in BA, that is, early detection of the disease, is also present in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Kasai portoenterostomy, a surgical procedure that restores bile flow within 30 days of life, could slow disease progression and prevent the need for liver transplants (4,5). However, BA is typically diagnosed at an average age of 40-50 days, making it challenging to confirm it in its early stages (6,7).…”
Section: Introductionmentioning
confidence: 99%